PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI PADA BANK SYARIAH YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2018-2020) - Ahmad Ridwan; Dedy Takdir Syaifuddin; Sujono Sujono (Pascasarjana Universitas Halu Oleo, 2023)
Although the Islamic banks is still limited, its value has grown by 5.29%. But the value is relatively cheap. The health factor of bank is the most essential, involve: Risk Profile, Good Corporate Governance, Earning, Capital and Company Size, so the purpose of this study is to test the effect of NPF, foreign exchange to equity, gross income exposure, self-assessment GCG, ROA, CAR and firm size on firm value as proxied by Tobin's q.The research sample includes 10 banks in IDX, consisting of 3 Islamic Commercial Banks and 7 Commercial Banks that have Sharia Business Units, in order to obtain 30 units of analysis. Multiple regression analysis using Eviews version 12. The results showed that: 1) NPF had negative but insignificant effect on firm value, 2) foreign exchange to equity had positive but insignificant effect on firm value, 3) gross income exposure had positive but insignificant effect on firm value. , 4) self-assessment GCG has significant negative effect on firm value, 5) ROA has positive but insignificant effect on firm value, 6) CAR has positive but insignificant effect on firm value, 7) firm size has significant positive effect on firm value.